PROGRAM PENGEMBANGAN BUKU SAKU EDUKATIF DALAM MENINGKATKAN MINAT BELAJAR HURUF HIJAIYAH PADA ANAK USIA DINI DI PERUM GPA DESA NGIJO KEC. KARANGPLOSO - Novitasari, Dian; Yuti, Ashory; Romelah, Romelah (Lembaga Pengkajian dan Pengembangan Masyarakat, Yayasan Cahaya Mulia Mandiri, 2025)
Purpose of the study: The purpose of this activity is to improve literacy in reading and writing Hijaiyah letters among early childhood in the recidential complex GPA Ngijo Village, Karangploso District. Methodology: The implementation method uses a qualitative approach with design-based research through the stages of needs analysis, design, product development, implementation, and field evaluation. Main Findings: Al-Qur'an reading and writing lessons for early childhood in recidential complex GPA Desa Ngijo Kec, Karangploso are still conducted conventionally without any innovative learning media. Applications of this study: This community service is useful for the community in recidential complex GPA Desa Ngijo Kec, Karangploso to be able to learn Hijaiyah letters easily through an educational pocket book program. Novelty/Originality of this study: The community in recidential complex GPA, Ngijo Village, Karangploso Subdistrict, can improve their ability to read and write Hijaiyah letters in early childhood through educational pocket books.